Clinical relevance for lowering C-reactive protein with statins. (2nd October 2016) - Arévalo-Lorido, José Carlos
Abstract: The role of statins in the protection of atherosclerosis and reducting cardiovascular (CV) events is well established. On the other hand, the role of inflammation in the propagation and propensity to CV events has also been demonstrated. High-sensitivity C-reactive protein (CRP) which is involved in the immunologic process of inflammation has received the interest for its use in screening and risk reclassification. However, evidence for its causal relationship with atherothrombosis is lacking, and even more, knowing that statins influence on the reduction of CRP levels, a relevant evidence of their clinical benefits in this regard is also lacking. This article reviews four different key points regarding the issue, to better understand the current state and application of the treatment with statins in order to achieve benefits from lowering CRP's levels regarding CV diseases: (1) the mechanisms of reduction of CRP levels by statins; (2) the role of statin-mediated CRP reduction in the atherosclerotic plaque regression; (3) the role in the prevention of CV diseases; and (4) the role in case of secondary prevention. With this basis, the reduction of CRP levels should be interpreted as a reduction of inflammatory burden thus its clinical benefits could be more interesting in secondary prevention. KEY MESSAGES: It could be admitted a role of statin-mediated CRP diminution to reduce the rate of progression in atherosclerotic plaque. In general, and in the absence of specific clinical trials, the role of statins by lowering CRP and consequently, preventing cardiovascular events may be superior in case of secondary prevention because a more pronounced state of inflammation and regardless of its levels at baseline.